Effectiveness of complementary food formulated from soybean seed coat and milkfish flour in supporting weight gain among young children - Lindawati; Yunita Sari; Cucuk Kunang Sari; Bangun Wijanarko; Dewi Indah Sari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Child undernutrition remains a significant concern in Indonesia, particularly during the complementary feeding period when inadequate dietary quality may impair optimal growth. Purpose: To evaluate the short-term effectiveness of a complementary feeding formulation composed of soybean seed coat flour and milkfish flour in supporting weight gain among children aged 9–12 months. Method: A quasi-experimental one-group pretest–posttest design was conducted among 20 children, with 16 included in the final analysis after excluding dropouts and outliers. Participants received 125 ml of the formulated complementary food daily for nine consecutive days. Body weight was assessed before and after the intervention. Results: Due to non-normal data distribution (Shapiro–Wilk p < 0.05), the Wilcoxon Signed Rank Test was applied. Seven children demonstrated weight gain, seven showed no change, and two experienced slight weight loss. Despite positive tendencies, the overall change was not statistically significant (Z = −1.727; p = 0.08). Factors such as short intervention duration, inconsistent caregiver adherence, concurrent intake of ultra-processed foods, and minor illnesses likely contributed to limited measurable changes. Conclusion: Although not statistically significant, the nutrient-rich formulation shows potential for longer-term application, especially in low-resource settings. Extended duration studies with larger sample sizes are recommended.